A Lexical and Syntax Checker Tool for the Hyper Text Markup Language - Abdul-Hussain, Maisaa Ibrahem (Al-Nahrain Journal of Science, 2011)
Hyper Text Markup Language (HTML) is one of the web sites design languages in the internet. HTML language differs from programming languages in that any editor (e.g. notepad, WordPad) can be used to write the code of the HTML language. On the other hand, and contrary to what one familiar with the role of the compiler while translating the high-level written code, this editing facility has a shortcoming of not being able to check the lexical and the syntax of the written HTML code. While any compiler takes into its responsibility to check for any lexical and syntax error as a part of its overall function, the interpreter of HTML provides the facility to translate the form of HTML codes to the target representation to be executed only. For this, the main aim of this paper is to propose and present an intermediate stage -semi compiler- to check the lexical and syntax of an HTML code before delivering it to the interpreter.